Minimally invasive autopsy – endoscopic approach to post-mortem diagnostics - Paweł Świderski; Szymon Rzepczyk; Beata Bożek; Czesław Żaba (Videosurgery and Other Miniinvasive Techniques)
The noticeable decline in the number of autopsies performed in recent years requires investigation into the causes of the phenomenon and attempts to prevent it. One potential cause of this trend is fear of disfiguring the body. Carrying out autopsies using a minimally invasive method may reduce the decrease in the number of autopsies performed. The first work on the development of the method and its continuation gave promising results. This allows us to start a discussion on attempts to introduce the method. The solution seems especially justified when the alternative is to completely abandon post-mortem examinations using the traditional method. Laparoscopy and thoracoscopy are tools that allow for accurate imaging and analysis of organ changes. Enriching them with additional tests using endoscopic techniques may have a positive impact on the accuracy of autopsy diagnoses. The development of a clear protocol for minimally invasive post-mortem diagnosis requires further research to determine the accuracy of the method.